Differences in HIV testing and receipt of results between adolescent and non‑adolescent women in Uganda - Ediru, Stephen; Wamala, Robert; Kwagala, Betty (AIDS Research and Therapy, 2019)
Despite notable increase in HIV testing among Uganda’s women from 25% in 2006 to 71% in 2011, HIV testing among adolescent women remains very low at 45.5%. This study assesses differences in HIV testing and receipt of results (HTR) between adolescent and non-adolescent women in Uganda. The differences were decomposed into components attributed to variation in characteristics and variation in effects of characteristics in the two groups. The assessment was based on data sourced from 2011 Uganda Demographic Health Survey. Statistical analysis was done using a Non-linear Oaxaca’ Blinder Multivariate Decomposition of the logistic regression. In the results, the difference in HIV testing and receipt of result between adolescent and non-adolescent women was significantly (P < 0.05) attributed to both variation in characteristics (57.2%) and variation in the effects of characteristics/coefficients (42.8%). In particular, the gap in HTR was mainly attributed to variation in characteristics such as ever had sex (34.7%) and ever given birth (31.6%) and variation in effects of characteristics such as education level (− 68.8%) and marital status (− 12.6%). Based on the findings of the study, government and other development partners need to scale up HIV testing programs targeting adolescents through tackling stigma, increasing on community outreach services and expanding adolescent friendly HIV services center.
Keywords: HIV testing; Receipt; Result; Adolescents; Non-adolescents; Decomposition